Modifying the methods of treatment of mothers of the mentally handicapped - a field study in the psychological center - Karima SI BACHIR; Karima SACI (Social Sciences Journal, 1970)
The study aimed to amend the mothers’s abnormal treatment of their children who developmental retardation, through the proposed- counseling program. It also aimed to provide them withinformation, educational experience and concepts about the nature of this mental retardation.Moreover, it highlights the characteristics of these children aiming at encouraging these women toaccept their children and their illness by providing them with special skills of training. Theresearcher adopted the method of the collective guidance because it provides the exchange ofexperience, the unity of purpose and opportunities to express their reaction in an acceptablemanner. It also achieves good results with regard to learning, leading to agreement on commonsolutions by the group, fosters confidence and mutual cooperation between the participants. Thesample study was made up of 15 mentally-retarded children’s mothers. The women were randomlychosen while the program was applied for 8 weeks. Besides, the duration of each session was (60)minutes. After the implementation of the program, the researcher adopted the dimensionalapproach to identify the continuity‘s extent of the program. The research relied on the DependentSample T-Test in order to examine the significant differences of the average level with regard tothe parental treatment’s methods. Hence, it resulted in the following .There are statisticallysignificant differences at the average level of the methods of parental treatment between pre andمجلة العلوم االجتماعية العدد 22 جانفي 2017 137pro evaluations due to the application of the counseling program. Thus, applying the program canamend the mothers’s treatment methods to their children. There are statistically significantdifferences at the average level of the methods of parental methods between pre and follow- upevaluations due to the application of the counseling program to the mothers of mentally-retartedchildren